Aprendizaje de la programación de computadores basado en PBL y emparejamiento por cuadrantes del modelo 4Q (2018)
The present article presents and analyzes the results obtained from a research inspired by a methodology to explore improvement ways for computer programming Learning based on the Problem Based Learning strategy and the application of the 4Q model preferences with work in pairs with opposite quadrants. To achieve this, the students were analyzed in reference to their preferences of thinking from a formal instrument known as the Benziger questionnaire. The brained results allow to visualize a different perspective with the students when working in pairs taking advantage of the benefits of a model of preferences of thought within the frame of the learning of computer programming. These results enable a detailed analysis of the progress of each pair of students. It concludes that working with pairs of students in the development of the activities of a programming subject can become a highly effective strategy as long as a thought preference model is known and applied appropriately.